REFORMASI HUKUM TATA KELOLA KESEHATAN DAERAH DALAM ERA DESENTRALISASI : TANTANGAN HARMONISASI REGULASI NASIONAL DAN LOKAL - Zulkifli Usman; Adipradana R Taha; Husnandi S Wange (Law Journal (LAJOUR), 2026)
This study analyzes the problems of regional health governance in the era of decentralization characterized by regulatory disharmony between Central and local governments. Research gap this study lies in the lack of studies that examine health governance issues from the perspective of normative construction and authority-sharing design, because most of the previous research focused on aspects of policy implementation or empirical case studies. The purpose of this study is to formulate the direction of reforming the regional health governance law that is able to overcome the fragmentation of authority and financing within the framework of decentralization. This study uses a purely normative juridical method with a legislative and conceptual approach through an analysis of Law Number 23 of 2014, Law Number 1 of 2022, and Law Number 17 of 2023. The results showed that the main problem of regional health management lies not in regional capacity alone, but in the design of laws that are fragmented and uncoordinated, causing uncertainty about the authority, financing, and responsibility of the state. This study provides a normative contribution by developing the concept of coordinated decentralization, which is a decentralized model that places regional autonomy within an integrated, standardized national policy framework, and accompanied by a clear coordination and accountability mechanism. This concept was formulated as a response to the condition of institutional fragmentation trap, a situation of fragmentation of authority and financing that mutually weaken the performance of health services. These findings are important as a basis for updating administrative law and health law to ensure the fulfillment of the right to health in a fair and sustainable manner.